New medium for isolating iron-oxidizing and heterotrophic acidophilic bacteria from acid mine drainage. - Manning, H L (1975)
A new solid medium is described for growing iron and heterotrophic bacteria from acid mine drainage (AMD). Examination of AMD from five states revealed several kinds of colonies of iron-oxidizing bacteria: (i) smooth, (ii) smooth with secondary growth sectors or branching, (iii) star-shaped, (iv) radiating lobe, and (v) flat-rough. All AMD samples yielded whitish colonies that could not use ferrous iron, sulfur, or hydrogen, nor could they grow on nutrient agar, brain heart infusion agar, or Trypticase soy agar. Glucose and sucrose supported growth if the sugar-salts medium was at pH 3.0. The new iron medium has several advantages over others: (i) easy preparation, (ii) rapid growth, (iii) larger colonies, (iv) differentiation of colony morphology, and (v) detection of a new group of heterotrophic acidophilic bacteria.